2021
DOI: 10.4300/jgme-d-20-00985.1
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence Supporting a Novel 10-Item Clinical Learning Environment Quick Survey (CLEQS)

Abstract: Background The clinical learning environment (CLE) is a priority focus in medical education. The Accreditation Council for Graduate Medical Education Clinical Learning Environment Review's (CLER) recent addition of teaming and health care systems obligates educators to monitor these areas. Tools to evaluate the CLE would ideally be: (1) appropriate for all health care team members on a specific unit/project; (2) informed by contemporary learning environment frameworks; and (3) feasible/quick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the PLCS has the highest Beckman et al (2005) total validity score among other questionnaires, followed by the Johns Hopkins Learning Environment Scale (JHLES). Evaluating the validity evidence of the questionnaires in the included articles based on the profession for which they were originally developed demonstrated that Clinical Learning Environment Quick Survey (CLEQS) (Simpson et al, 2021), followed by DREEM (Roff et al, 1997) scored the highest among the questionnaires developed for the medical profession. Whereas the Clinical Learning Environment, Supervision and Nurse Teacher (CLES + T) Scale (Saarikoski et al, 2008), the Clinical Learning Environment and Supervision (CLES) instrument (Saarikoski & Leino-Kilpi, 2002), and the Clinical Learning Environment Diagnostic Inventory (CLEDI) (Hosoda, 2006) scored the highest among questionnaires developed for the nursing profession, followed by the Clinical Learning Environment Comparison Survey (CLECS) (Leighton, 2015).…”
Section: Interpretation Ofmentioning
confidence: 99%
“…Furthermore, the PLCS has the highest Beckman et al (2005) total validity score among other questionnaires, followed by the Johns Hopkins Learning Environment Scale (JHLES). Evaluating the validity evidence of the questionnaires in the included articles based on the profession for which they were originally developed demonstrated that Clinical Learning Environment Quick Survey (CLEQS) (Simpson et al, 2021), followed by DREEM (Roff et al, 1997) scored the highest among the questionnaires developed for the medical profession. Whereas the Clinical Learning Environment, Supervision and Nurse Teacher (CLES + T) Scale (Saarikoski et al, 2008), the Clinical Learning Environment and Supervision (CLES) instrument (Saarikoski & Leino-Kilpi, 2002), and the Clinical Learning Environment Diagnostic Inventory (CLEDI) (Hosoda, 2006) scored the highest among questionnaires developed for the nursing profession, followed by the Clinical Learning Environment Comparison Survey (CLECS) (Leighton, 2015).…”
Section: Interpretation Ofmentioning
confidence: 99%
“…Although the practice of thoughtfully educating future physicians has a history dating back to Hippocrates, medical education as a field where the scholarship of teaching and learning is debated, studied and implemented has yet to develop firm foundational principles. For instance, the field's literature offers many examinations of the complexities shaping every level of the educational continuum-from preclinical to clinical undergraduate medical education (UME) [19][20][21][22] and from the clinical learning environment in graduate medical education (GME) [22][23][24] to the varied practices addressed by continuing professional development (CPD). 25 Furthermore, as recently as 2022, Maggio et al 3 reported their efforts, and indeed their struggles, to delineate the field of medical education via the use of three bibliometric approaches.…”
mentioning
confidence: 99%